Pencurian Dalam Presfektif Hukum Pidana Islam - Muhammad Afriza Rifandy; Muhammad Defri; Syaifullah Syaifullah; Surya Sukti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
As the main source of law in Islam, the Qur'an has described various types of criminal offenses and their punishments, which are called Jarimah. This is relevant to the aim of enacting God's laws on this earth for the benefit and happiness of humans themselves. The provisions of sanctions that Allah gives to the perpetrator of the abuse are not intended to take revenge for what he has done, but rather to fulfill the rights of Allah and the rights of the persecuted family as a form of justice, providing a deterrent effect and protecting the public. As amukallaf, humans should obey and submit to the sharia rules that Allah has established in the Qur'an in order to be safe from sanctions both in this world and in the afterlife. The crime of theft is a violation of social norms, both state legal norms and religious norms. Any religion does not justify its followers stealing, because it will be detrimental to the victim and social order (Iqbal, 2021). In the Indonesian Criminal Code, the crime of theft is written in the Criminal Code (KUHP), Volume XXII II, Articles 362-367, Crime of Property, which has various types and sanctions for theft. (Lutfi, Kurniaty, Basri, & Krisnan, 2022). According to crime statistics published by BAPPENAS, the level of property crime or theft in Indonesia increased during 2012-2013, with 25,036 cases in 2012 and 25,593 in 2013. (Aeni, 2021). If we look at other countries, countries that follow the rules of Islamic law, namely Saudi Arabia, the application and provisions of this country's laws are derived from the rules of the Islamic religion, which uses the Koran and Hadith as sources of law. to take the law. According to the Arab Social Defense Organization, Saudi Arabia has much lower rates of property or theft than in Arab countries such as Syria, Sudan, Egypt, Iraq, Lebanon and Kuwait, which do not implement Islamic criminal law. The rate of property crime or theft in these six countries is much higher, namely 650 times higher than Saudi Arabia. (Fitrah, 2021). The problem is that ordinary people do not have a deep understanding of Islamic criminal law. People will only feel that Islamic criminal law fines are sadistic, inhumane and violate human rights. It is believed that any theft must be sanctioned, or the punishment is amputation, although certain conditions must be met in Islamic law for amputation to be punishable. (Muhammad Wahyu, 2018). The Indonesian Criminal Code and Criminal Code have different legal systems and sanctions for perpetrators of theftAbstracts consist of abstracts in English and abstracts in Indonesian. The abstract uses Garamond letters (10 pt) with a word count of 150 to 300 words. Abstracts must be concise, clear and complete. The abstract must contain the research objectives, methods, results (findings) and recommendations.